Low‐Income Housing Development, Poverty Concentration, and Neighborhood Inequality. (14th July 2015) - Freedman, Matthew; McGavock, Tamara
Abstract: Considerable debate exists about the merits of place‐based programs that steer new development, and particularly affordable housing development, into low‐income neighborhoods. Exploiting quasi‐experimental variation in incentives to construct and rehabilitate rental housing across neighborhoods generated by Low‐Income Housing Tax Credit (LIHTC) program rules, we explore the impacts of subsidized development on local housing construction, poverty concentration, and neighborhood inequality. While a large fraction of rental housing development spurred by the program is offset by a reduction in the number of new unsubsidized units, housing investment under the LIHTC has measurable effects on the distribution of income within and across communities. However, there is little evidence the program contributes meaningfully to poverty concentration or residential segregation.